1986
DOI: 10.1002/1097-0142(19860201)57:3<656::aid-cncr2820570343>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Production of and response to interleukin-2 in peripheral blood lymphocytes of cancer patients

Abstract: Interleukin-2 (IL2) is essential for the expansion of antigen-triggered lymphocytes and cytotoxic T-cells, processes necessary for tumor control that are frequently depressed in malignancy. The authors measured certain aspects of IL2 function in cancer patients and controls and correlated the findings with the general immune response as indicated by the proliferative response to phytohemagglutinin (PHA) in peripheral blood lymphocytes (PBL). The major questions focused on the capacity of PBL to produce IL2, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Measurements of cytokine production in cell cultures have also been used to determine the immunological activity of breast cancer patients, but here the results were controversial. In one study, an impaired production of TNF was found (Zielinski et al, 1990) and a defective expression and release of the IL-2 receptors (Hakim, 1988), while in another study the production of IL-2 was not diminished (Wanebo et al, 1986). In lymphocyte cultures of patients with endometrial carcinomas a reduced IL-2 production has been described (Yron et al, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Measurements of cytokine production in cell cultures have also been used to determine the immunological activity of breast cancer patients, but here the results were controversial. In one study, an impaired production of TNF was found (Zielinski et al, 1990) and a defective expression and release of the IL-2 receptors (Hakim, 1988), while in another study the production of IL-2 was not diminished (Wanebo et al, 1986). In lymphocyte cultures of patients with endometrial carcinomas a reduced IL-2 production has been described (Yron et al, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on human cancer patients have revealed defects in both IL-1 production (38) and IL-2 production (39), in some patients. In some, lymphocyte responsiveness to IL-2 seemed to be impaired (39). Factors of the sort described here might well be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 is a short-lived lipid-based signaling molecule with potent localized paracrine and autocrine functions that is particularly important for tumor development. PGE2 has been shown to promote tumor angiogenesis (38,71), drug resistance (36), invasion and migration (35), immune suppression (24,72,73), and the inhibition of apoptosis (34). PGE2 is generated by tumors and tumor-associated immune cells from arachidonic acid, with the rate-limiting step being the enzymatic activity of cyclo-oxygenase 2 (COX-2).…”
mentioning
confidence: 99%